APLIKASI FUZZY INFERENCE SYSTEM METODE MAMDANI UNTUK REKOMENDASI PEMILIHAN BIDANG KAJIAN PADA MAHASISWA PROGRAM STUDI MATEMATIKA UNSOED - Yusuf Nur Assegaf; Mutia Nur Estri (Universitas Jenderal Soedirman, 2012)
This paper discusses about Fuzzy Inference System (FIS) using Mamdani method to recommend the choice of major field for students of Mathematics department Unsoed. The method of Mamdani consist of a fuzzification, an application of the implication functions, composition of rules, and defuzzification. The input of fuzzification is score of some compulsary subjects for each field. The application of implication function used min implication, while the composition rule is based on PAP in Mathematic department Unsoed. The defuzzification required score of some compulsary subjects for each field as input and the recommend score of each major field as output. Based on the output, a student of Mathematic department Unsoed is able to choose a major field according to his/her score.